STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage: Protocol for a randomised controlled trial. (December 2020) - Larsen, Kristin Tveitan; Forfang, Elisabeth; Pennlert, Johanna; Glader, Eva-Lotta; Kruuse, Christina; Wester, Per; Ihle-Hansen, Hege; Carlsson, Maria; Berge, Eivind; Al-Shahi Salman, Rustam; Bruun Wyller, Torgeir; Rønning, Ole Morten
Background and aims: Many patients with prior intracerebral haemorrhage have indications for antithrombotic treatment with antiplatelet or anticoagulant drugs for prevention of ischaemic events, but it is uncertain whether such treatment is beneficial after intracerebral haemorrhage. STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage will assess (i) the effects of long-term antithrombotic treatment on the risk of recurrent intracerebral haemorrhage and occlusive vascular events after intracerebral haemorrhage and (ii) whether imaging findings, like cerebral microbleeds, modify these effects. Methods: STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage is a multicentre, randomised controlled, open trial of starting versus avoiding antithrombotic treatment after non-traumatic intracerebral haemorrhage, in patients with an indication for antithrombotic treatment. Participants with vascular disease as an indication for antiplatelet treatment are randomly allocated to antiplatelet treatment or no antithrombotic treatment. Participants with atrial fibrillation as an indication for anticoagulant treatment are randomly allocated to anticoagulant treatment or no anticoagulant treatment. Cerebral CT or MRI is performed before randomisation. Duration of follow-up is at least two years. The primary outcome is recurrent intracerebral haemorrhage. Secondary outcomes include occlusive vascular events and death. Assessment of clinical outcomes is performed blinded to treatment allocation. Target recruitment is 500 participants. Trial status: Recruitment to STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage is on-going. On 30 April 2020, 44 participants had been enrolled in 31 participating hospitals. An individual patient–data meta-analysis is planned with similar randomised trials.